Who is a Victim? Difference and Accountability in Shani Mootoo’s Cereus Blooms at Night - Busse, Cassel (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Contributing to what Dominick LaCapra has identified as the institutionalization of trauma studies in the humanities, Margaret Atwood once identified survival, colonization, and hardship as the primary experiences of “Canadian-ness.” Many writers have since exposed fundamental flaws in this model. Shani Mootoo’s novel Cereus Blooms at Night provides clear examples of the ethical problems formed between witness and victim within an overarching framework of victimization. Here, perpetrators identify as victims, victims identify as perpetrators, and accountability becomes a blur. The narrator’s piecing together of fragmented memories and utterances problematically integrates multiple accounts into a single overarching voice that equates traumatic experience with a repetition of victimization. By crafting a narrative voice that is problematic, monologic, and ultimately appropriating, Mootoo illuminates weighty issues that strain the fabric of “trauma studies,” as well as social and political life more generally. She thus calls for a remapping of ethics in what Annette Wieviorka has described as “the era of the witness.”